NEW AND EFFECTIVE METHODS OF TEACHING ENGLISH TO ELEMENTARY SCHOOL PUPILS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In this article, you can find several modern and effective ways for teaching English to elementary school students and this methods presented in this article will help children learn English quickly and effectively. Every teacher faces challenges when teaching elementary grades, and the techniques in this and other articles can be of great help in overcoming them, because different exercises and games are more interesting for children than lessons